The English son [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Amish millionaire, 2016)
In the opening of a six-part serial novel, businessman Joel Byler has gotten himself into a financial bind and his eccentric, wealthy Amish father is done bailing out his spoiled son. Will Joel learn he must pay for his own mistakes -- and at what cost?